2007
DOI: 10.1111/j.1365-2435.2007.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

An ontogenetic perspective on the relationship between age and size at maturity

Abstract: Summary1. Understanding the relationship between age and size at maturity is essential because these traits are pivotal determinants of an organism's fitness. 2. The relationship between age and size is commonly addressed using optimization and quantitative genetic approaches. Here we argue that the value of such studies is often limited by an insufficient consideration of organismal ontogeny. 3. On the basis of a simple conceptual framework of hierarchical resource allocation, we identify key aspects of ontog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 88 publications
4
60
1
Order By: Relevance
“…Indeed, the transition from growth to reproduction produces an observable relationship between age and size at maturity (Berner and Blanckenhorn, 2007). In freeliving Norway rats (R. norvegicus) from temperate and tropical populations, both males and females reach sexual maturity at ~200 g (Porter et al, 2015), suggesting this as the critical weight threshold which triggers the physiological processes that underlie the reproductive life of the species (Berner and Blanckenhorn, 2007;Porter et al, 2015). Based on this, the rats fed ad libitum (FR-) reached that threshold between the 7th and 8th week of life, while those with limited resources (FR+) matured almost a month later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the transition from growth to reproduction produces an observable relationship between age and size at maturity (Berner and Blanckenhorn, 2007). In freeliving Norway rats (R. norvegicus) from temperate and tropical populations, both males and females reach sexual maturity at ~200 g (Porter et al, 2015), suggesting this as the critical weight threshold which triggers the physiological processes that underlie the reproductive life of the species (Berner and Blanckenhorn, 2007;Porter et al, 2015). Based on this, the rats fed ad libitum (FR-) reached that threshold between the 7th and 8th week of life, while those with limited resources (FR+) matured almost a month later.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, larger individuals are better able to compete for resources, usually have higher reproductive output, are less-likely to be predated and experience a lower cost of foraging reductions (Berner and Blanckenhorn, 2007;Muñoz and Bonal, 2008;Preisser and Orrock, 2012). In addition, individuals in a good body condition are better prepared to face and limit an infection .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of insect growth and associated physiological changes have in most instances found an observable relationship, either positive or negative, between body size and age at maturity (Nijhout, 2003;Stern, 2003;Berner & Blanckenhorn, 2007). The widely accepted physiological model of insect growth posits that size in insects is determined by the attainment of a size threshold in the final instar, the critical weight (or size), at which an irreversible endocrine cascade is triggered, characterised by a decline in juvenile hormone titres and an increase in ecdysteroid hormone levels, culminating in the initiation of metamorphosis (Nijhout, 2003).…”
Section: Physiological Explanations For Body Size Variationmentioning
confidence: 99%
“…The widely accepted physiological model of insect growth posits that size in insects is determined by the attainment of a size threshold in the final instar, the critical weight (or size), at which an irreversible endocrine cascade is triggered, characterised by a decline in juvenile hormone titres and an increase in ecdysteroid hormone levels, culminating in the initiation of metamorphosis (Nijhout, 2003). In the interval during which these changes are occurring in the final larval or nymphal instar, the insect continues to feed and grow and may almost double in size (Berner & Blanckenhorn, 2007). This model has been successful in explaining the relationship between size and age over a range of environmental and genetic factors (but not host plant quality, as far as we are aware) for a number of arthropod and vertebrate species, leading to a general conclusion that most multicellular organisms must acquire a specific amount of resources, manifested as size or weight thresholds, before they can enter reproductive life (Berner & Blanckenhorn, 2007).…”
Section: Physiological Explanations For Body Size Variationmentioning
confidence: 99%
See 1 more Smart Citation